Bolaño y Tlatelolco - Juan Antonio Sánchez Fernández (Études romanes de Brno, 2013)
Through the personage of Auxilio Lacouture, Bolaño turns to the Tlatelolco theme in two of his major works, Los detectives salvajes and Amuleto. Being the massacre of Tlatelolco (1969) one of the most important events of mexican contemporary history, it has produced a lot of bibliography, first of all novel and essay. The present paper compares Bolaño's view of that historical fact with those of Paz, Fuentes or Poniatowska. In the novelistic of the Chilean writer there are some rhetorical fundaments that relate it to postmodern fiction. Precisely this postmodern principles lend to Bolaño's conception of history a very different character, at the end of the century, than that of the literature of the seventies. The understanding of history as discourse and the lack of sense of human life are some of the manifestations of this spirit, in whose conception, Tlatelolco has a new profile; a profile that can be symptomatic of the perception of history of a whole generation.